Effects of virtual reality with different modalities on upper limb recovery: a systematic review and network meta-analysis on optimizing stroke rehabilitation - Jiali Zhang; Mingxiu Liu; Junlin Yue; Jinmei Yang; Yan Xiao; Jie Yang; Enli Cai (Frontiers in Neurology)
BackgroundAs a major cause of disability worldwide, stroke affects about 80% of survivors with upper limb (UL) motor dysfunction, significantly impairing their quality of life. Virtual reality (VR) has been recognized as an innovative rehabilitation tool; however, the effectiveness of VR systems with different immersion modalities is still uncertain. This systematic review and network meta-analysis (NMA) aims to evaluate the comparative effectiveness of intervention measures, including non-immersive gaming consoles, immersive VR (IVR), non-immersive VR (NIVR), and conventional therapy (CT) on upper limb motor function in stroke rehabilitation.Materials and methodsA systematic search of PubMed, Embase, Cochrane Library, and Scopus identified randomized controlled trials (RCTs) published up to 12 June 2024. UL motor recovery was assessed using the Fugl-Meyer Upper Extremity (FMUE) scale. The NMA was performed using the Bayesian approach with the BUGSnet package in R software to calculate the relative effectiveness of each intervention.Results34 RCTs involving 1,704 participants were included. Among non-immersive gaming systems, Microsoft Kinect demonstrated the greatest effective in enhancing UL motor function, followed by Nintendo Wii, then NIVR and IVR head-mounted devices. CT showed the least effective. Specifically, Microsoft Kinect significantly improved FMUE scores (mean difference [MD] = 7.27, 95% confidence interval [CI]: 0.59 to 13.77, p < 0.05), followed by Nintendo Wii (MD = 4.53, 95% CI: 0.87 to 8.14, p < 0.05), and NIVR (MD = 3.57, 95% CI: 1.18 to 6.01, p < 0.05). In contrast, IVR head-mounted devices showed no statistically significant differences in outcomes, with MD of 4.16 (95% CI: −0.02 to 8.38).ConclusionNon-immersive gaming console of Microsoft Kinect is the most effective intervention for improving UL motor function in stroke survivors. In contrast, IVR head-mounted devices did not offer significant advantages over CT. These findings suggest that non-immersive gaming consoles of Microsoft Kinect could be a more cost-effective and accessible alternative for stroke rehabilitation.